Research on the Path of Revitalizing and Inheriting Rural Intangible Cultural Heritage from the Perspective of Cultural Governance - Wang, Pei; Liu, Zheng (Transactions on Social Science, Education and Humanities Research, 2024)
Intangible cultural heritage is an important component of national culture, carrying rich historical information and cultural connotations. From the perspective of cultural governance, through a series of active and effective strategies and measures, provide sustained support and development momentum for the inheritance of rural intangible cultural heritage. At the same time, sorting out the revitalization and inheritance path of rural intangible cultural heritage can also achieve and promote the modernization of rural social governance capacity, and improve the level and effectiveness of rural social governance.